Impact of Zero Cost Books Adoptions on Student Success at a Large, Urban Community College - Smith, Nathan D.; Grimaldi, Phillip J.; Basu Mallick, Debshila (Frontiers in Education, 2020)
This article examines the impact of Zero Cost Textbooks (ZCB) courses on two key factors of students success: pass rates and completion rates. We examine three years of data at Houston Community College, ending with the first year of their implementation of a ZCB program. Following the "access hypothesis," we suppose that students who would not otherwise be able to purchase traditional textbooks will have higher pass rates and completion rates in ZCB courses. We use Pell recipient status and ethnicity as proxies for socio-economically disadvantaged students, targeting those populations where the access hypothesis will have the greatest impact. We isolate faculty who taught both ZCB and non-ZCB courses during the period under review and conduct a post-hoc analysis, using mixed effects logistic regression, to identify interactions between student and course characteristics and success metrics. We find that HCC's ZCB program had a statistically significant positive effect on pass rates for all students, but no effect on completion. We find a trend to suggest the ZCB program may improve success among Black students, but only a statistically significant positive effect among Asian students, and no interaction with Pell recipient status. These results are not well explained by the access hypothesis; they suggest the need for further research.